Journal of Human Sport and Exercise - 2020 - Spring Conferences of Sports Science 2020
DOI: 10.14198/jhse.2020.15.proc3.05
|View full text |Cite
|
Sign up to set email alerts
|

The most effective physical exercise to reduce burnout syndrome in university students

Abstract: The objective of this study was to determine the most effective physical exercise in reducing burnout syndrome levels in university students. Methods: An experimental study was carried with 2 intervention groups with aerobic and strength exercise and one control group without exercise. Instruments: Maslach Burnout Inventory Students Survey and Heart Rate Variability (HRV): RR mean, SDNN, and RMSSD. Results: In exhaustion there was the greatest percentage of change in the aerobics group with a reduction of 26 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Several research studies [58][59][60][61][62][63][64] that have focused on the benefits of exercise in decreasing the effects of stress have documented this positive relationship. Many researchers have noted that yoga too provides numerous advantages.…”
Section: Discussionmentioning
confidence: 92%
“…Several research studies [58][59][60][61][62][63][64] that have focused on the benefits of exercise in decreasing the effects of stress have documented this positive relationship. Many researchers have noted that yoga too provides numerous advantages.…”
Section: Discussionmentioning
confidence: 92%
“…Gurupriya R, exposed that yoga exercise decreases HRV and releases stress in undergraduate medical students 17 . May RW estimated that various biofeedback interventional pragrammes improve cognitive performance with increased HRV in undergraduate college students with burnout [18][19][20] . Grässler B also testified improvement in HRV after various execises 4 .…”
Section: Discussionmentioning
confidence: 99%
“…In general, burnout can be interpreted as mental fatigue, depersonalization and decreased personal achievement in athletes [7,8,9]. Burnout can cause someone feel tired, unmotivated and listless [10,11]. Previous research reported that burnout level can increase when athletes experienced excessive training hours [12,13], intense competition schedules [14,15], injuries [16], decreased performance [5], resulting in a negative impact on mental and physical health [17], and sport carrers termination [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…If you don't have a mattress, you can use a mat or newspaper, and you should prepare a candle so that meditation can be conducted optimally. If all of this equipment does not exist, there will be a shortage and will have an impact on the ineffectiveness of this training" (Results of interviews with participants10,5,17,22,11,8). Burnout has always been a problem for us when carrying out intense training and competition schedules, so we emphasized that mindfulness programs could reduce burnout level (Results of interviews with participants 3, 6, 9, 10, 13, 16).…”
mentioning
confidence: 99%